2014
DOI: 10.1007/s10535-013-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids and their role in response of plants to abiotic stresses

Abstract: Brassinosteroids (BRs) are polyhydroxylated steroidal plant hormones that play pivotal role in the regulation of various plant growth and development processes. BR biosynthetic or signaling mutants clearly indicate that these plant steroids are essential for regulating a variety of physiological processes including cellular expansion and proliferation, vascular differentiation, male fertility, timing senescence, and leaf development. Moreover, BRs regulate the expression of hundreds of genes, affect the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(109 citation statements)
references
References 74 publications
4
97
0
8
Order By: Relevance
“…BR and GA are vital hormones in plant that influence various developmental processes, such as cell division, cell elongation, flowering, leaf senescence, and seed germination (Greenboim-Wainberg et al, 2005;Vriet et al, 2013;Fariduddin et al, 2014;Sakata et al, 2014;Hedden and Sponsel, 2015). BR and GA interact with each other at both biosynthesis and signaling levels to form a potential complex network Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…BR and GA are vital hormones in plant that influence various developmental processes, such as cell division, cell elongation, flowering, leaf senescence, and seed germination (Greenboim-Wainberg et al, 2005;Vriet et al, 2013;Fariduddin et al, 2014;Sakata et al, 2014;Hedden and Sponsel, 2015). BR and GA interact with each other at both biosynthesis and signaling levels to form a potential complex network Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This positive action is generally correlated with higher expression of stress marker genes, indicating that increased expression of stress responsive genes is responsible, at least in part, for the higher stress tolerance in BR-treated plants (Vardhini and Anjum 2015). In addition, it has been shown that application of BRs activates antioxidative pathways, including ROS-scavenging systems, as well as, non-enzymatic antioxidants, such as osmolytes like proline, glycine betaine, sorbitol, mannitol, and reduced glutathione, ascorbic acid that are needed for osmotic adjustment, stabilization of membranes, and ROS-scavenging (Fariduddin et al 2014). However, it is still unclear whether BRs, directly or indirectly, modulate the responses of plants to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Весьма существенно, что брассиностероиды увеличивают устойчивость ряда растений к неблагоприятным температурам, высокому содержанию в почве тяжелых металлов, избыточному засолению и др. [Ефимова и др., 2014;Fariduddin et al, 2014]. Вместе с тем, механизмы стресс-протекторного, в том числе, и солезащитного действия стероидных фитогормонов в настоящее время изучены недостаточно.…”
Section: мв ефимоваunclassified
“…Вместе с тем, механизмы стресс-протекторного, в том числе, и солезащитного действия стероидных фитогормонов в настоящее время изучены недостаточно. Кроме того, защитный эффект гормонов обычно оценивают при его совместном действии с повреждающим фактором [Fariduddin et al, 2014;Siddiqui et al, 2018]. Имеются немногочисленные работы, в которых предпринимаются попытки более фундаментального подхода при изучении гормональной регуляции физиологических процессов при стрессе у растений [Ефимова и др., 2016, 2018a; Кузнецов и др., 2016].…”
Section: мв ефимоваunclassified